Public Relations as A Mechanism for Improving Police Community (A Case Study of Dansoman) - Yiadom, Nana Adarkwah (UniMAC - GIJ, 2020)
Community relation is an important tool in every establishment, Public relations is very paramount to the community. It seeks to introduce a friendly atmosphere for organization and community to work together as partners in progress. Any establishment situated in a community owes the community cordiality and vise-versa. It should be the situation if the two are to exist in a conducive atmosphere. Good public relations an save an organization from liquidations in terms of crisis and poor public relations may result to the fold up of a healthy organization. Full information of police public relations in Dansoman and its relations with the community can bring regards to the police administration for it good work to the community. Once this positive impression is not registered in the minds of the people in the community, the police organization’s reputation is bound to be dented. The measure of successful public relation will be indicated by the regards which people have for an organization. Regards based on the knowledge and understanding that has been created within the community.
THESIS